Nanoscale magnonic Fabry-Pérot resonator for low-loss spin-wave manipulation - Huajun Qin (Nature Portfolio, 2021)
Compared to electromagnetic waves, the wavelength of spin waves is significantly shorter at gigahertz frequencies, enabling the miniaturisation of wave-based devices. Here, the authors present a magnonic Fabry-Pérot resonator allowing for nanoscale and reconfigurable manipulation of spin waves.